Exploring the Internet Integrating technology into the classroom (for teachers) - Nebraska Educational Telecommunication Network; Great Plains National Instructional Television Library (New York: GPN, 1990)
Explains how teachers, library media specialist, and educational can integrate the internet into the classroom, lesson plans
Host: Reggi Carlson, John Snell
Keywords: Internet (Computer network) in education; Internet (Computer network).; Internet in education